Teachers matter: linking teachers and students’ self-regulated learning - Karlen, Yves; Hertel, Silke; Grob, Urs; Jud, Johannes; Hirt, Carmen Nadja (Research papers in education, 2024)
Teachers play an essential role in supporting students to become self-regulated learners. It is assumed that teachers’ professional competence in self-regulated learning (SRL) influences their promotion of SRL, which in turn influences students’ acquisition of SRL skills. However, the links between teachers’ SRL competences, SRL promotion, and students’ SRL have not yet been the subject of extensive research. In a multilevel analysis with 167 lower secondary teachers and their 2,785 students, we examined the relationships between teachers’ professional competences (own SRL skills, mindsets, pedagogical content knowledge about SRL, self-efficacy, and attainment values), teachers’ self-reported and students’ perceived SRL promotion, and students’ SRL skills (metacognitive, motivational, and cognitive strategies, and metacognitive strategy knowledge). The results highlight the importance of teachers’ self-efficacy for their self-reported SRL promotion. Furthermore, SRL promotion was positively related to students’ metacognitive, motivational, and cognitive strategies but not to their metacognitive strategy knowledge. The analyses of indirect effects showed that teachers’ own SRL as self-regulated learners and their self-efficacy as agents of SRL were indirectly related to students’ SRL through the promotion of SRL. Focusing on teachers’ SRL competences as both learners and agents could help to understand better why teachers do or do not promote SRL, thereby explaining the development of students’ SRL.